Salmonella Typhimurium lacking phoBR as a live vaccine candidate against poultry infection - Jung, Bogyo; Park, Soyeon; Kim, Eunsuk; Yoon, Hyunjin; Hahn, Tae Wook (Veterinary Microbiology, 2022)
Salmonella enterica serovar Typhimurium, with a broad-host range, is a predominant cause of non-typhoidal Salmonella infection in humans, and the infectious source is highly associated with food animals, especially poultry. Considering the horizontal transmission of S. Typhimurium from farm animals to humans, vaccination has been strongly recommended in industrial animals. In an effort to eradicate S. Typhimurium in poultry farms, a live candidate vaccine strain lacking the phoBR genes, which encode the PhoB/PhoR two-component regulatory system responsible for cellular phosphate signaling, was evaluated in mice and chickens. Lack of the phoBR genes promoted overgrowth of intracellular Salmonella. However, notably, in BALB/c mouse models, the ΔphoBR mutant showed attenuated virulence and instead, provided protection against infection with virulent Salmonella, thereby clearing out Salmonella in the spleen and liver. Accordingly, immunization with the ΔphoBR mutant increased immunoglobulin (Ig)G and IgM antibody responses and also tended to increase the IgG2a/IgG1 ratio, which is indicative of T helper (Th)1-mediated cellular immunity. In chicken challenge models, immunization with the ΔphoBR mutant significantly boosted the production of IgG and IgM antibodies after the second vaccination. The vaccinated chickens ceased fecal shedding of challenged Salmonella earlier than the non-vaccinated ones and showed no Salmonella in their caecum and ileum. These results demonstrate the potential of the S. Typhimurium ΔphoBR mutant as a vaccine in chickens.
Keywords: Animals; Chickens; Mice; Poultry; Rodent Diseases; Salmonella Infections; Salmonella Infections, Animal; Salmonella typhimurium; Salmonella Vaccines; Vaccines, Attenuated; Immunogenicity; phoBR; Protective efficacy; Salmonella Typhimurium; Vaccine